Reason for joining the medical profession: passion or parental pressure - Malik, Rohma; Ashfaq, Urwa; Aziz, Beshair; Khan, Allahdad; Zafar, Ayesha; Jamil, Muhammad Farhan (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the factors that influence medical students’ decision to pursue a career in medicine, and to assess their level of satisfaction with their decision. Method: The descriptive, cross-sectional study was conducted at the Nishtar Medical University, Multan, Pakistan, from July to October 2023, and comprised first year medical students of the 2023-24 academic session. Data was collected using a questionnaire-based survey form. Data was analysed using SPSS 23. Results: Of the 174 students with mean age 20.1+-1.4 years, 93(53.4%) were males with mean age 19.9+-1.5 years, and 81(46.6%) were females with mean age 20.3+-1.2 years (p>0.05). For 121(69.5%) students, ‘parental pressure’ was the primary factor, followed by ‘passion’ for 41(23.6%), ‘inspired by others’ 3(1.7%), ‘noble profession’ 2(1.1%), ‘monetary gains’ 3(1.7%) and ‘just by chance’ 4(2.3%). There were 26(14.9%) subjects who had conducted thorough research before deciding to pursue the profession. For 85(48.9%) students, personal interest played a minor role in career selection. Overall, 88(50.6%) students were completely satisfied with the decision, 12(6.9%) had concerns, and 74(42.5%) were dissatisfied. Conclusion: A significant number of students entered the medical profession under parental pressure. Only about half of the students were satisfied with their decision. Key Words: Students, Medicine, Career choice, Medical students, Motivation.